2011
DOI: 10.1002/app.34405
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of recycled poly(ethylene terephthalate) and polypropylene blends: Effect of polypropylene molecular weight on homogeneity and compatibility

Abstract: ABSTRACT:The effectiveness of compatibilizers in enhancing the dispersion of polypropylene (PP) at various molecular weights in recycled polyethylene terephthalate (RPET) was elucidated. The idea of incorporating PP of different molecular weights evolved from the intention of simultaneously recycling the PET bottles together with the PP-based bottle caps, which are often of low molecular weight (M w ). Three grades of PP with known molecular weights were blended with RPET at various loadings of compatibilizers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Polypropylene (PP)/poly(ethylene terephthalate) (PET) blends with PP as the major phase are widely studied and used in many application areas, especially in packaging materials 1–6. For example, flexible intermediate bulk containers (FIBCs), a typical PP/PET blend in which the PET content is about 10 wt %, are widely used in the industry for the transport and storage of powders, granules, or pellets 7–9.…”
Section: Introductionmentioning
confidence: 99%
“…Polypropylene (PP)/poly(ethylene terephthalate) (PET) blends with PP as the major phase are widely studied and used in many application areas, especially in packaging materials 1–6. For example, flexible intermediate bulk containers (FIBCs), a typical PP/PET blend in which the PET content is about 10 wt %, are widely used in the industry for the transport and storage of powders, granules, or pellets 7–9.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the fillers such as talc or CaCO 3 were used in order to improve the thermal resistance and flame retardancy of RPET/RPP blends [5]- [9]. Inoya et al [10] [11] has reported on hydrogenated block-copolymer of SEBS for improving the compatibility of R-PET with PP blends. Many investigations had been performed on polymer blends involving RPET bottles from post-consumer waste PET bottles with discarding caps and labels.…”
mentioning
confidence: 99%
“…As expectable, adding the SEBS rubbery compatibilizer caused an increase of ductility and impact resistance. Since 15 phr of compatibilizer is a too high amount in terms of costs, another way is to change the PP molecular weight (Inoya et al 2012). In this case, lower molecular weight PP helps with the diffusion of the compatibilizer inside the melt and the maximization of its concentration at the interface, allowing the reduction of the compatibilizer amount.…”
Section: With Polymers Different From the Recycled Onementioning
confidence: 99%
“…Some authors (Inoya et al 2008;Inoya et al 2012) studied the effect of the compatibilizer level (SEBS) on the mechanical properties of r-PET/PP blends. The addition of up to 15 phr of compatibilizer resulted in a size reduction of the dispersed phase, while a slight increase in density suggested an improvement on interfacial interactions.…”
Section: With Polymers Different From the Recycled Onementioning
confidence: 99%